Resistance training is linked to heightened positive motivational state and lower negative affect among healthy women aged 65–70. (3rd September 2018) - Ericson, Helena; Skoog, Therése; Johansson, Mattias; Wåhlin-Larsson, Britta
ABSTRACT: Resistance training (RT) improves overall health, but the psychological effects of RT in healthy old adults have not been tested. The aim of this study was to investigate a sample of 65–70-year-old healthy and physically active women to assess their sense of coherence, health-related quality of life, hope, and affect, before and after taking part in a 24-week RT intervention ( N  = 14), compared to controls ( N  = 18). Findings showed a significant increase in hope ( p  = 0.013) and a significant decrease in negative affect ( p  = 0.002). Starting RT after age 65 does not appear to negatively impact on women's psychological health but seems to be associated with important psychological health benefits.